Kompetisi antara Ekotipe Echinochloa crus-galli pada Beberapa Tingkat Populasi dengan Padi Sawah (Competition of Echinochloa crus-galli Ecotypes at Several Populations Against Lowland Rice) - Dwi Guntoro; Muhamad Achmad Chozin; Edi Santosa; Soekisman Tjitrosemito; Abdul Harris Burhan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Echinochloa crus-galli is a major weed in paddy field that reduces rice yield.  The objective of the research was to study the effect of E. crus-galli ecotypes and populations on rice growth and production.  The research was conducted in a green house using split plot design with three replications.  The main plot consisted of three E. crus-galli ecotypes i.e ecotype from Karawang, Cikampek, and Sukabumi. E. crus-galli population as sub plot consisted of 0, 1, 2, 3, and 4 E. crus-galli per pot.  The results showed that ecotype of E. crus-galli affected plant height, number of tiller, and panicle density. The competitivenes against rice of E. crus-galli ecotype Cikampek was higher than that of ecotype Sukabumi and Karawang. Population E. crus-galli affected rice growth and production.  Population of E. crus-galli 4/pot decreased spikelets weight about 48.0% and filled spikelets weight about 46.2%.  Interaction of ecotype and population of E. crus-galli did not affect rice growth and production.   Key words:  competition, ecotype, E. crus-galli, population, weed.